A Case of Urethral Duplication Arising from the Posterior Urethra to the Scrotum with Urinary Stone in a 6-Year-Old Male - Kenichi Mori; Toshitaka Shin; Shohei Tobu; Mitsuru Noguchi; Yasuhiro Sumino; Fuminoi Sato; Hiromitsu Mimata (Case Reports in Pediatrics)
Urethral duplication is a rare congenital anomaly. We report a 6-year-old male with type IIA2 (Y-type) using Effmann’s classification. The accessory urethra, in which a urinary stone existed, arose from the posterior urethra to the scrotum. Because of recurrent urinary tract infection and urinary discharge from the accessory urethra, surgical removal of the accessory urethra through a scrotal incision was performed. At 7-month postoperative follow-up the patient was completely free from urinary incontinence and urinary tract infection.